HUBUNGAN STATUS GIZI DENGAN PERKEMBANGAN MOTORIK KASAR PADA ANAK USIA 1-3 TAHUN DI POSYANDU SYUKUR NIKMAT DESA SUNGAI DUREN - Fidiya Sela Fitri; Rosmaria Rosmaria (NHM PRESS, 2021)
Toddler age children are children aged 12-36 months (1-3 years). In this period children are trying to find out how things work and how to control others through anger, rejection, and stubbornness. at this time it will cause irreversible damage and can have an impact on brain development. This research is an analytic study with a cross sectional design. The purpose of this study was to determine the relationship between nutritional status and gross motor development in children aged 1-3 years. The population in this study were children aged 1-3 years totaling 123 and the sample in this study was 123 using the total sampling technique. The study was conducted from January 2021 to September 2021. The statistical test used in this study was to use the chi-square test. The results of the study showed that 110 (89.4%) respondents had good nutritional status, as many as 111 (90.2%) respondents had normal gross motor development, there was a relationship between nutritional status and gross motor development in children aged 1-3 years with a p value = 0.000 For this reason, nutritional status is important for children's gross motor development so that children can grow and develop according to their age It is hoped that the Syukur Nikmat Posyandu can provide health education about balanced nutrition for children aged 1-3 years so that children can meet body nutrition so that children's development can be optimal.